2022
DOI: 10.1038/s41598-022-23815-4
|View full text |Cite
|
Sign up to set email alerts
|

Inducer-free cellulase production system based on the constitutive expression of mutated XYR1 and ACE3 in the industrial fungus Trichoderma reesei

Abstract: Trichodermareesei is a widely used host for producing cellulase and hemicellulase cocktails for lignocellulosic biomass degradation. Here, we report a genetic modification strategy for industrial T.reesei that enables enzyme production using simple glucose without inducers, such as cellulose, lactose and sophorose. Previously, the mutated XYR1V821F or XYR1A824V was known to induce xylanase and cellulase using only glucose as a carbon source, but its enzyme composition was biased toward xylanases, and its perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…Previous studies revealed that the expression of Xyr1 with the constitutive promoter tcu1 or pdc1 led to glucose-blind cellulase hyperproduction but not that of β-glucosidase and xylanase. , Unlike WT Xyr1, Xyr1 A824V and Xyr1 V821F mutants resulted in significantly improved xylanase production but weak activation of cellulase expression . We report here that the constitutive expression of Xyr1 R434L improves the production of both cellulolytic enzymes, including cellobiohydrolases, endoglucanases, β-glucosidases, and xylanolytic enzymes.…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…Previous studies revealed that the expression of Xyr1 with the constitutive promoter tcu1 or pdc1 led to glucose-blind cellulase hyperproduction but not that of β-glucosidase and xylanase. , Unlike WT Xyr1, Xyr1 A824V and Xyr1 V821F mutants resulted in significantly improved xylanase production but weak activation of cellulase expression . We report here that the constitutive expression of Xyr1 R434L improves the production of both cellulolytic enzymes, including cellobiohydrolases, endoglucanases, β-glucosidases, and xylanolytic enzymes.…”
Section: Resultsmentioning
confidence: 61%
“…12,25 Unlike WT Xyr1, Xyr1 A824V and Xyr1 V821F mutants resulted in significantly improved xylanase production but weak activation of cellulase expression. 39 We report here that the constitutive expression of Xyr1 R434L improves the production of both cellulolytic enzymes, including cellobiohydrolases, endoglucanases, β-glucosidases, and xylanolytic enzymes. Consistent with the master regulatory role of Xyr1, 40,41 Xyr1 R434L with improved transcriptional activity enhances the expression of a suite of cellulolytic and xylanolytic enzymes in T. reesei.…”
Section: Constitutive Expression Of Xyr1 R434l Boosted Both Cellulase...mentioning
confidence: 82%
“…The expression system of lactic acid bacteria has gained attention due to its stable expression level and efficient expression of target proteins [33]. Constitutive expression systems are particularly advantageous as they exhibit consistent expression levels under varying environmental conditions, thereby eliminating the need for inducers [34]. The present study reports the construction of a recombinant strain, namely pPG-LFCA-E/LR-CO21 (LR-LFCA), utilizing LimosiLactobacillus reuteri as a carrier for expressing LFCA, a compound that possesses both probiotic and antimicrobial peptide properties [11].…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps the most remarkable (well-documented) example of strain engineering is the development of the RUT-C30 cellulase hyperproducer prototype strain, which is derived from strain QM6a, and shows a 20-fold increase in extracellular protein levels, reaching about 30 g/L on a lactose-containing growth medium ( Bischof et al , 2016 ). Recent tools such as RNAi-mediated gene silencing ( Sun et al , 2022 ), inducer-free expression systems ( Arai et al , 2022 ), CRISPR/Cas9-based methods ( Rantasalo et al , 2019 , Fonseca et al , 2020 ) and synthetic expression systems with engineered transcription factors and promoters ( Rantasalo et al , 2018 ) provide new tools for engineering cellulase production strains ( Mojzita et al , 2019 ). For example, Arai et al (2022) reported an inducer-free expression system for T. reesei that enables protein overproduction in glucose– containing media without inducers like cellulose, lactose and sophorose.…”
Section: Engineering Cellulase Cocktailsmentioning
confidence: 99%
“…Recent tools such as RNAi-mediated gene silencing ( Sun et al , 2022 ), inducer-free expression systems ( Arai et al , 2022 ), CRISPR/Cas9-based methods ( Rantasalo et al , 2019 , Fonseca et al , 2020 ) and synthetic expression systems with engineered transcription factors and promoters ( Rantasalo et al , 2018 ) provide new tools for engineering cellulase production strains ( Mojzita et al , 2019 ). For example, Arai et al (2022) reported an inducer-free expression system for T. reesei that enables protein overproduction in glucose– containing media without inducers like cellulose, lactose and sophorose. In another study, Fonseca et al (2020) used CRISPR/Cas9-based rational engineering of the RUT-C30 strain to increase protein secretion and β-glucosidase (72-fold) and xylanase (42-fold) activities in the secretome.…”
Section: Engineering Cellulase Cocktailsmentioning
confidence: 99%